Smart Pet Feeder on Cat Food Portions Using Mamdani's Fuzzy Logic Inference System Method - Muhammad Ayat Hidayat; Suriandi Jayakrista (Journal of Computer Engineering, Electronics and Information Technology, 2023)
This is a system that can help cat owners provide the right amount of food for their cats. This system uses the Mamdani fuzzy logic inference system method which can process input in the form of information about the cat's body weight and make a decision about the amount of food to be given to the cat. This system is integrated with a smart pet feeder called FoodyPet which can dispense food according to the decision made by the system. By using this system, cat owners can easily provide the right amount of food for their cats and maintain their cat's health. In addition, this system can also help cat owners automatically schedule their cat's meal times so they don't have to worry about forgetting to give food to their cats. This system consists of several main components, namely Arduino UNO as a microcontroller that runs all data processing processes, an loadcell as a tool to measure the cat's body weight, an ultrasonic sensor as a tool to measure the level of food in the tank, and an LCD display used to display information about the food portion to be given to the cat. This system is also equipped with a buzzer that will signal the cat owner when the food is ready to be given to the cat.